2005
DOI: 10.1093/eurheartj/ehi845
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey on acute heart failure in cardiology ward services in Italy

Abstract: Acute HF is an ominous condition, needing more research activity and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
179
4
15

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(219 citation statements)
references
References 28 publications
21
179
4
15
Order By: Relevance
“…Vascular diseases and particularly heart failure at discharge were associated to readmission, in agreement with previous observations on the predictive role of diseases of the circulatory system [12] and particularly of heart failure [25]. Also liver diseases were associated with readmission, in agreement with a previous study based upon 30-day readmission [7].…”
Section: Discussionsupporting
confidence: 91%
“…Vascular diseases and particularly heart failure at discharge were associated to readmission, in agreement with previous observations on the predictive role of diseases of the circulatory system [12] and particularly of heart failure [25]. Also liver diseases were associated with readmission, in agreement with a previous study based upon 30-day readmission [7].…”
Section: Discussionsupporting
confidence: 91%
“…The length of hospital stay of our patients was comparable to that found in other European registries [29][30][31][32]. Our patients who developed WRF had a longer duration of hospital stay and this may be important both with respect to quality of life and the cost of treatment.…”
Section: Clinical and Prognostic Value Of Wrfsupporting
confidence: 82%
“…Several investigators have reported on the in‐hospital mortality in patients with acute heart failure, which is an ample concept that includes acute decompensation of chronic heart failure, cardiogenic shock with or without pulmonary edema, right ventricular failure, and APE 3, 6, 14, 19, 20, 21. In these studies, mortality has varied from 6.4% to 17.2% and they have shown advanced age,6, 14, 19, 21 severe left ventricular dysfunction,14 acute coronary syndromes,14 admission blood pressure,6, 19, 21 renal failure,6, 19, 21 need for inotropics,19 and anemia19 as principal predictors.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, mortality has varied from 6.4% to 17.2% and they have shown advanced age,6, 14, 19, 21 severe left ventricular dysfunction,14 acute coronary syndromes,14 admission blood pressure,6, 19, 21 renal failure,6, 19, 21 need for inotropics,19 and anemia19 as principal predictors.…”
Section: Discussionmentioning
confidence: 99%